WAKAF SAHAM PERSFEKTIF HUKUM ISLAM DAN HUKUM POSITIF SERTA PRAKTIKNYA DI BADAN WAKAF INDONESIA (BWI) DAN GLOBAL WAKAF (STAI Darussalam Lampung, 2023)
The purpose of this article is to discuss stock waqf. This research uses qualitative research and literature, in the method of data analysis, the author uses comparative qualitative research methods, the results of the study state that stock waqf is equated with the law like the law of cash waqf, because both have the potential for great benefit if represented, the law of stock waqf is allowed considering that shares have the permanence of benefits that can continue to be reaped as long as the company issuing the shares runs its business well, while the principal value of the shares is maintained. According to the MUI Sharia Council Fatwa, the Compilation of Islamic Law, and the Accounting And Auditing Organization For Islamic Financial Institutions (AAOIFI), stock waqf is allowed, because it is one of the types of securities waqf. In the positive legal review stipulated in the Waqf Law No. 41 of 20014, Government Regulation No. 42 of 2006, and Minister of Religious Affairs Regulation No. 73 of 2013, stock law is included in the category of waqf objects of movable securities. Shares that can be waqfed are sharia shares and conventional shares. The permissibility of waqf of conventional shares of permissible companies needs to be further regulated. Because in practice there is no detailed regulation regarding the criteria and mechanism of stock waqf, the practice of implementing stock waqf carried out by BWI and Global Wakaf is not the same in its implementation, especially related to the process and mechanism of stock waqf.